Conference Essay: The Field of Discourse Research in the Process of Becoming Established - Susann Fegter; Antje Langer (Forum: Qualitative Social Research, 2008)
Over the last decade, interdisciplinary discourse research in the tradition of Michel FOUCAULT has been evolving constantly in the German-speaking world. It also takes linguistic methodologies as a point of orientation and establishes itself in the framework of qualitative social research. At the international interdisciplinary conference "Language—Power—Knowledge" in Augsburg from 10 – 12 October 2007, participants explored and discussed the current state of discourse theory and analysis. With the present conference essay, we intend to provide insight into the discussions that took place there. We first outline the questions and goals of the conference, and then present a brief summary of the lectures. A number of focal points emerged at the conference that were taken up repeatedly and discussed in a variety of contexts: the relation between discourse analysis and critique, the relation between the subject (subjectivity) and discourses, the relation between power, discourse and dispositive, and the relation between discourse analyses and visuality. In systematizing these four points, we undertake a critical consideration of the "results" of the conference. In conclusion, we highlight two current network initiatives on interdisciplinary discourse research that were introduced at the conference. URN: urn:nbn:de:0114-fqs0802181